PEMANFAATAN KALIUM FERRAT DALAM PENGOLAHANLIMBAH PEWARNA BLUE DIRECT 2B - Nita Kusumawati, Rida Nurhayati dan (Universitas Negeri Yogyakarta, 2012)
An investigation on synthesis of potassium ferrate and its applicationin degradation of Blue direct 2B. The purpose of this research is to studydegradation influence of optimal pH and optimal Molar ratio from kaliumferrat for degradation blue direct 2B. The investigation were performed withsynthesis and characterization of potassium ferrat before it was reacted withblue direct 2B.The result a kuantity of reaction was followed by UV-Visspectrophotometry. pH for research is 9 – 10 and molar ratio of kaliumferrat : blue direct 2B is 1 : 1 – 5 : 1.From the research, the stability of kalium ferrat for degradation bluedirect 2B in the optimal pH 9,6 and the optimal molar ratio ferrat : bluedirect 2B in 1 : 1 – 5 : 1 the result of degradation is 96,32% after 30minutes. It kown if the wavelength shift from 610 nm to 298,80 nm, so thecolour of solvent change from blue-green to yellow transparent (until notcoloured). It conclused if the wavelength or the colour change is showchange of compound structure it consequenced of degradation withpotassium ferrat.